Alendronate therapy in cyclosporine-induced alveolar bone loss in rats - Rossa, C. (Blackwell Publishing, 2007)
Background and Objective: Cyclosporine A is an immunosuppressive drug that is widely used in organ transplant patients as well as to treat a number of autoimmune conditions. Bone loss is reported as a significant side-effect of cyclosporine A use because this can result in serious morbidity of the patients. As we have shown that cyclosporine A-associated bone loss can also affect the alveolar bone, the purpose of this study was to evaluate the effect of the concomitant administration of alendronate on alveolar bone loss in a rat model.Material and Methods: Forty Wistar rats (10 per group) were given cyclosporine A (10 mg/kg, daily), alendronate (0.3 mg/kg, weekly), or both cyclosporine A and alendronate, for 60 d. The control group received daily injections of sterile saline. The expression of proteins associated with bone turnover, including osteocalcin, alkaline phosphatase and tartrate-resistant acid phosphatase (TRAP), and also the calcium levels, were evaluated in the serum. Analysis of the bone volume, alveolar bone surface, the number of osteoblasts per bone surface and the number of osteoclasts per bone surface around the lower first molars was also performed.Results: the results indicate that cyclosporine A treatment was associated with bone resorption, represented by a decrease in the bone volume, alveolar bone surface and the number of osteoblasts per bone surface and by an increase in the number of osteoclasts per bone surface and TRAP-5b. These effects were effectively counteracted by concomitant alendronate administration.Conclusion: It is concluded that concomitant administration of alendronate can prevent cyclosporine A-associated alveolar bone loss.
Keywords: alendronate; alveolar bone loss; biochemical markers of bone turnover; cyclosporine